Adverse Events Following Pneumococcal Vaccination among Infants attending Immunization Clinic at a Tertiary Hospital in Northern India - Goswami, Shweta; Gupta, Shefali; Singh, Mitasha; Gupta, Ekta (Indian Journal of Community Health, 2020)
Background: Pneumococcal conjugate vaccine (PCV-13) has been introduced in India in a phased manner. In Haryana it was introduced in 2017. The adverse events following immunization (AEFI) with PCV in real community setting are yet to be detected. Objective: To calculate the incidence and associated factors for various AEFI after pneumococcal vaccination at a tertiary centre of Faridabad, Haryana. Methodology: The descriptive observational study was conducted from April through October 2019 at the immunization centre of a tertiary care centre of Faridabad, Haryana. Each dose of PCV-13 given to the infants attending immunization centre was the study unit. A telephonic contact was done within 24 hours, after 48 hours and between 5-7 days to enquire about any adverse events (minor & major), if occurred. Results: A total of 135 PCV-13 doses were followed up for any AEFIs. 113 AEFIs (incidence: 67.3 per 100 dose) reported in 93 infants. Incidence of fever was 45 per 100 dose followed by tenderness and erythema (39 per 100 doses for each). Incidence of Swelling was 21 per 100 doses. Conclusion: Active surveillance and co administration of Pentavalent vaccine could have resulted in higher proportion of AEFIs.